Effects of different drying methods on drying kinetics and physicochemical properties of Chrysanthemum morifolium Ramat - Li, Borui; Lin, Jueyi; Zheng, Zhian; Duan, Hao; Li, Dong; Wu, Min (International Journal of Agricultural and Biological Engineering, 2019)
The effects of infrared-assisted hot-air drying (IR-HAD), temperature, humidity controlled hot-air drying (THC-HAD), and hot-air drying (HAD) on the drying kinetics, physicochemical properties, chlorogenic acid content and microstructure of chrysanthemum were experimentally examined. The results showed that the drying time reduced with increasing air drying temperature, with IR-HAD needing the shortest drying time, followed by THC-HAD and HAD. The effective moisture diffusivities (Deff) of chrysanthemum under IR-HAD, THC-HAD, and HAD at 60°C were 3.22×10-9 m2/s, 2.19×10-9 m2/s, and 2.89×10-9 m2/s, respectively. IR-HAD preserved chrysanthemum surface color better than THC-HAD and HAD, whereas the THC-HAD samples obtained higher water holding capacity (WHC), water binding capacity (WBC), and chlorogenic acid content. Additionally, peroxidase (POD) residual activity of the samples decreased with increasing blanching time. The current work provides a theoretical basis for the drying of chrysanthemum. Keywords: chrysanthemum, drying kinetics, Weibull model, physicochemical properties, peroxidase (POD) residual activity, chlorogenic acid content DOI: 10.25165/j.ijabe.20191203.4820 Citation: Li B R, Lin J Y, Zheng Z A, Duan H, Li D, Wu M. Effects of different drying methods on drying kinetics and physicochemical properties of Chrysanthemum morifolium Ramat. Int J Agric & Biol Eng, 2019; 12(3): 187–193.